MAJOR EVENT MANAGEMENT STRATEGIES IN STRENGTHENING TELKOM UNIVERSITY'S REPUTATION (CASE STUDY: TELKOM UNIVERSITY ANNIVERSARY SDGS FOR INDONESIA) - Muhamad Reynaldi Satria Nugraha; Mohamad Syahriar Sugandi (RADJA PUBLIKA, 2025)
This research analyzes the major event management strategy, specifically of the Telkom University Anniversary